Application Effect of Computer-Assisted Local Anesthesia in Patient Operation. (13th November 2021) - Hao, Yuchen; Zhang, Zheqi; Meng, Yan
Abstract : In order to avoid the psychological harm caused by pain to patients, in this study, the application effect of computer-assisted local anesthesia in patient surgery was studied. In this method, 72 patients with hypertension, 35 males and 37 females, aged 53–83 years, with an average age of 70.8 ± 1.3 years, were selected for appointment tooth extraction in the department of stomatology from January to December 2014. All patients were booked for tooth extraction by ECG monitoring. Patients who were contraindicated for tooth extraction, had a history of mental illness, and had used antianxiety drugs and sedatives within 1 week before surgery were excluded. Patients were randomly divided into two groups according to their ID numbers: observation group, 36 cases, and control group. Painless oral local anesthesia injection instrument was used for local anesthesia injection. In the control group, 36 patients were injected with local anesthesia by traditional manual injection. The results showed that 86.11% of patients in the observation group had decreased anxiety scores after anesthesia, while only 13.88% of patients in the control group had decreased anxiety scores. Among patients with decreased anxiety scores, 80.65% in the observation group became nondental anxiety compared with 28.57% in the control group. Computer-assisted oral local anesthesia can effectively control dental anxiety and relieve the pain and discomfort of local anesthesia injection, and improve patient satisfaction, conducive to the smooth nursing work.